HUBUNGAN ANTARA TINGKAT PENDIDIKAN DENGAN PEMAHAMAN TENTANG PENGELOLAAN LIMBAH RUMAH TANGGA BAGI ANGGOTA KELOMPOK WANITA TANI DI DESA RIANIATE - Sitanggang, Reny Furnawati; Kurniawan, Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to: (1) determine the educational level of members of the Women's Farmer Group in Rianiate Village; (2) examine their level of understanding of household waste management; and (3) analyze the relationship between educational level and understanding of household waste management. This research employed a quantitative approach using an correlational design. The sample consisted of 31 members of the Women's Farmer Group, selected using a total sampling technique. Data were collected through questionnaires and analyzed using descriptive statistics and the Pearson Product-Moment correlation test. The findings revealed that the respondents' educational level was generally in the moderate category, with most participants having completed primary and secondary education. Their understanding of household waste management was categorized as high, although the trend analysis indicated that the level of understanding was not evenly distributed among respondents. Furthermore, the Pearson Product-Moment correlation analysis yielded a correlation coefficient (r) of 0.610 with a significance value of 0.000 (p < 0.05), indicating a positive and statistically significant relationship between educational level and understanding of household waste management. These findings suggest that higher educational attainment is associated with a better understanding of household waste management among members of the Women's Farmer Group.